Host species, range extensions, and an observation of the mating system of Atlantic shallow-water gall crabs (Decapoda: Cryptochiridae) - Van Der Meij, S (University of Miami, Rosenstiel School of Marine and Atmospheric Science, 2014)
Coral-associated invertebrates dominate the biodiversity of coral reefs. Some of the associations involving symbiotic invertebrates remain unknown or little studied. This holds true even for relatively wellstudied coral reefs, like those in the Caribbean Sea. Coral gall crabs (Cryptochiridae), obligate symbionts of stony corals, form a much-overlooked component of coral reef communities. Most recent studies on the Atlantic members of Cryptochiridae have been conducted off Brazil and little recent data have become available from the Caribbean region. During fieldwork off Curaçao (southern Caribbean Sea), eight new host coral species, belonging to four coral families, were recorded for three cryptochirid species. Kroppcarcinus siderastreicola Badaro, Neves, Castro and Johnsson, 2012, previously only known from Brazil, and Opecarcinus hypostegus (Shaw and Hopkins, 1977) are new additions to the fauna of Curaçao. Besides the new hosts and geographic range extensions, a free-living male Troglocarcinus corallicola Verrill, 1908 was observed visiting a female of the same species lodged in her gall in an Orbicella annularis (Ellis and Solander, 1786) colony. This is the first photodocumented record of the "visiting" mating system in Cryptochiridae.